Tempted to Text: College Students' Mobile Phone Use During a Face-to-Face Interaction With a Close Friend. (December 2016) - Brown, Genavee; Manago, Adriana M.; Trimble, Joseph E.
We examined whether emerging adults would engage in mobile phone use (MPU) when given the opportunity to socialize face-to-face with a close friend in a laboratory setting. Sixty-three U.S. college student friendship dyads rated their friendship quality in an online survey before coming into the laboratory together. When they arrived for their appointment, they were asked to wait together in a room for 5 min. A hidden camera recorded each dyad. Friends then separately rated the quality of the interaction. We coded time spent using mobile phone in seconds. A hierarchical regression conducted at the level of the dyad controlling for friendship quality and gender showed that more MPU was associated with lower quality interactions. We discuss findings in terms of the potential for MPU to interfere with the development of friendship intimacy.